The Impact of the Project-Based Learning Model on Students' Critical and Creative Thinking Skills in Science and Physics Learning: A Meta-Analysis - Nur Hikmah; Dhea Febriya; Asrizal Asrizal; Fatni Mufit (Postgraduate, University of Mataram, 2023)
This research is a meta-analysis to see the influence of the Project-Based Learning (PjBL) model in learning science and physics on students' critical and creative thinking skills. The method used is meta-analysis with a population and research sample, namely scientific articles that have been published through Google Scholar on a national to international scale in 2016–2023, that discuss the application and influence of the PjBL model in learning science and physics on students’ critical and creative thinking skills. Overall, the results of the research show that the application of the PjBL model in learning science and physics has an influence in the high category, both on students' critical and creative thinking skills. In the school-level category, the implementation of the PjBL model had the highest effect on students' critical thinking skills at university levels. Whereas in terms of creative thinking skills, the implementation of PjBL has the highest influence at the elementary school levels. In the subject category, the application of the PjBL model has a high effect on both critical thinking skills and creative thinking when applied to science and physics subjects.